Harmoniousness in connecting music and visual artworks in the Slovenie ! and Finnish cultural environment - Črčinovič Rozman, Janja (Muzikološki zbornik, 2011)
Music and visual artworks can contain same elements and principles of design. These elements influence the personal appreciation of artworks. The results of empirical investigation into the experiences and reactions of Slovene and Finnish students of elementary education in both fields of art show some differences in connecting four musical and visual artworks in accordance with the cultural environment of the students.
Keywords: glasbena in likovna umetniška dela; harmoničnost; harmoniousness; music and visual artworks; Slovenie and Finnish students; slovenski in finski študenti